Gene of the month: T-cell immunoreceptor with immunoglobulin and ITIM domains (TIGIT). Issue 4 (20th January 2022) - Bolm, Louisa; Petruch, Natalie; Sivakumar, Shivan; Annels, Nicola E; Frampton, Adam Enver
Abstract : Immune modulators play a crucial role in carcinogenesis and cancer progression by impairing cancer cell-targeted immune responses. T-cell immunoreceptor with immunoglobulin and immunoreceptor tyrosine-based inhibitory motif domains (TIGIT) regulates T-cell function and cancer cell recognition and was therefore identified as a promising target for cancer immunotherapy. TIGIT is expressed in T cells and natural killer (NK) cells and has three ligands: CD155, CD112 and CD113. CD155 binds TIGIT with the highest affinity and promotes direct and indirect downregulation of T-cell response. TIGIT signalling further inhibits NK function and secretion of proinflammatory cytokines. An association between TIGIT expression and poor survival was identified in multiple cancer entities. Blocking TIGIT with monoclonal antibodies, and a combination of TIGIT and programmed cell death protein 1 blockade in particular, prevented tumour progression, distant metastasis and tumour recurrence in in vivo models. Inhibition of TIGIT is currently evaluated in first clinical trials.